Sintesis dan Karakterisasi Garam Rangkap Kupri Amonium Sulfat Heksahidrat (Cu(NH4)2(SO4)2.6H2O) - Mia Baizura; Nadila Khairunnisa; Salsabila Hasna Putri; Widya Rahayu Putri (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
This research focuses on the synthesis and characterization of the double salt copper(II) ammonium sulfate hexahydrate, Cu(NH4)2(SO4)2·6H2O. The study aims to obtain the compound in crystalline form and evaluate its properties through yield calculation, solubility testing, and Fourier Transform Infrared (FTIR) spectroscopy. The synthesis involved reacting copper(II) sulfate pentahydrate (CuSO4·5H2O) with ammonium sulfate ((NH4)2SO4) under controlled conditions, followed by crystallization. The process produced 10.84 grams of crystalline Cu(NH4)2(SO4)2·6H2O with an 86.23% yield, indicating efficient synthesis. Solubility tests showed that the crystals were polar, soluble in polar solvents like water and hydrochloric acid (HCl), partially soluble in ammonium hydroxide (NH4OH), and insoluble in less polar solvents like ethanol and chloroform (CHCl3). FTIR analysis confirmed the presence of functional groups such as O–H, N–H, and S–O stretching vibrations, supporting the proposed molecular structure. The findings demonstrate that Cu(NH4)2(SO4)2·6H2O can be efficiently synthesized, and its physicochemical properties align with theoretical expectations. This study contributes to the understanding of double salt synthesis and characterization, relevant for inorganic chemistry, material science, and potential applications in catalysis and coordination chemistry.